Continual low-level MEK inhibition ameliorates cardio-facio-cutaneous phenotypes in zebrafish - Corina Anastasaki; Katherine A. Rauen; E. Elizabeth Patton (The Company of Biologists, 2012)
SUMMARY Cardio-facio-cutaneous (CFC) syndrome is caused by germline mutations in KRAS, BRAF and MEK1/2. The highly selective and potent MEK inhibitors that have been developed as anti-cancer agents hold potential as therapeutics for CFC syndrome. We have previously shown that the effects of CFC mutations on zebrafish gastrulation can be prevented by a 1-hour treatment with MEK inhibitors within a specific developmental time-window. However, MEK activity is essential for normal development and PD0325901 treatment outside this treatment window leads to additional developmental defects in MEK-dependent tissues. We now test ten different doses of PD0325901 at six developmental time points and assess the effects on body axis length, heart development and craniofacial structures in zebrafish embryos. Notably, we find that a continuous low-level dose of PD0325901 that has only minor inhibition of MEK activity can prevent the action of both the common CFC BRAFQ257R kinase-active allele and the BRAFG596V kinase-impaired mutant allele through the first 5 days of development. These results provide a detailed study of the effects of PD0325901 in development and show that, unlike in cancer, which requires robust inhibition of MAPK signalling, a partial reduction in phospho-ERK1/2 activity is sufficient to moderate the developmental effects of BRAFCFC mutations.